Health economics of health justice partnerships: A rapid review of the economic returns to society of promoting access to legal advice - Granger, Rachel; Genn, Hazel; Tudor Edwards, Rhiannon (Frontiers in Public Health, 2022)
Background: Welfare legal problems and inadequate access to support services follow both the socioeconomic and the health inequalities gradients. Health Justice Partnership (HJP) is an international practitioner-led movement which brings together legal and healthcare professionals to address the root causes of ill health from negative social determinants. The aim of this paper was to identify the current evidence base for the cost-effectiveness of HJP or comparable welfare advice services. Methods: A rapid review format was used, with a literature search of PubMed, CINAHL, ASSIA, PsycINFO, Medline, Cochrane Library, Global Health and Web of Science identifying 496 articles. After removal of duplicates, 176 papers were screened on titles and abstracts, and 20 papers met the eligibility criteria. Following a full-text screening, a further 14 papers were excluded due to lack of economic evaluations. Excluded papers’ reference lists were scanned, with a further 3 further papers identified which met the inclusion criteria. A final pool of 9 studies were included in this review. Results: Studies focused on the financial benefit to service users, with only 3 studies reporting on cost effectiveness of the interventions. Only 1 study reported on the economic impact of change of health in service users and 1 study reported on changes in health service use. Conclusion: This review highlights the current evidence gap in evaluating the cost-effectiveness of adequate access to free legal welfare advice and representation. We propose that an interdisciplinary research agenda between health economics and legal-health services is required to address this research gap.